A developing educational psychology service work-allocation model. Issue 2 (3rd April 2018) - Marsh, Alan J.; Higgins, Andrea
Abstract: As UK governments continue with the economic policy of deficit reduction from 2010, many Local Authorities' (LAs) Educational Psychology Services (EPSs) have begun to develop "traded" models of service delivery in order to maintain jobs and secure services. Nevertheless, EPSs still provide a core service delivery to schools, settings and geographical patches for statutory and pre-statutory work, which needs to be equitably distributed within the team to apportion demands and workloads. This article will discuss how a work-allocation model has developed in recent years, with reference to case studies from three diverse LAs.